From Madrasah to Muamalah: Enhancing Islamic financial literacy in Bekasi's pesantren community - Sufyati, Sufyati; Melati, Melati; Nurjaya, Nunu; Suryanti, Heni; Nur, Muhammad; Syamsudin, Syamsudin (Indonesian Journal of Business, Accounting and Management, 2023)
This community service is intended to improve Indonesian society's Islamic banking and financial literacy. Community service is conducted through through hybrid Meetings (virtual and On-site) targeted at vocational high school students at Barokah Darurrohman Islamic Boarding School, Sukawangi, Bekasi. This community service is expected to increase the number of people who access and use Islamic financial and banking products through increasing Islamic financial and banking literacy so that, in the end, they can contribute to the growth and development of Indonesia's Islamic finance and banking industry. Based on the analysis that has been done, this community service activity can be declared to have been held successfully because the targets of material, activity objectives, and participants' mastery of the material have been successfully achieved. Note: This article serves as a restored version of the original content following a corruption incident. The Digital Object Identifier (DOI) has been successfully re-registered and reactivated to ensure continued accessibility and citation integrity.